Some Brief Notes on Kai Māori - Rangiwai, Byron (Te Kaharoa, 2021)
Food is a signifier of identity and status (Hayden, 1998, 2009; Hayden & Villeneuve, 2011; Neill et al., 2015). In traditional times, Māori consumed a range of hunted, gathered, and cultivated foods (Royal & Kaka-Scott, 2013). As a result of this diet, non-infectious diseases were low among Māori due to foods with higher levels of protective chemicals and nutrients (Cambie & Fergusson, 2003).